A Case of Hemophagocytic Lymphohistiocytosis During Immune Checkpoint Inhibitor Treatment for Metastatic Renal Cell Carcinoma, Complicated by Pancytopenia Attributed to Cytomegalovirus Infection - Tomoko Honda; Hirohito Naito; Yu Osaki; Yoichiro Tohi; Yuki Matsuoka; Takuma Kato; Homare Okazoe; Rikiya Taoka; Nobufumi Ueda; Mikio Sugimoto (IJU Case Reports)
ABSTRACT Introduction Hemophagocytic lymphohistiocytosis (HLH) is characterized by macrophage and cytotoxic lymphocyte hyperactivation, fever, pancytopenia, liver dysfunction, and abnormal coagulation. However, no specific treatments have been established for HLH caused by immune checkpoint inhibitors. Case Presentation A 63‐year‐old male with clear cell renal carcinoma was treated with pembrolizumab and lenvatinib. Fifteen days later, he developed pancytopenia, liver and renal impairments, hypofibrinogenemia, hypertriglyceridemia, and elevated ferritin levels. Subsequently, he was admitted to the ICU for respiratory and circulatory instabilities. The patient was diagnosed with HLH and treated with high‐dose corticosteroids and mycophenolate mofetil. Pancytopenia persisted and required massive blood transfusions. Cytomegalovirus infection was found to be the cause, and pancytopenia improved with ganciclovir. The patient was discharged from the ICU after 21 days. Conclusion We present the case of a patient who developed HLH as an immune‐related adverse event along with a secondary cytomegalovirus infection, resulting in prolonged pancytopenia.